Unser Thüringen - Marten, Walter; Boas, Jasper G.; Fischer, Heinz; Koepp, Volker; Raue, Dieter (Die DDR in Originalaufnahmen, 2020)
Auf dieser DVD finden Sie Original-Dokumentationen der DEFA von 1955 bis 1986 über Thüringen. [Cover]